P-156 Patients, family & friends – shaping our hospice together. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Marley, Kate; Harvey, Gillian; Slocombe, Carole
Abstract : Introduction: Woodlands' 2013/14 Quality Account identified the development of a Patient, Family and Friends Forum as its patient experience priority. The objectives were to ensure: Current high standards of care were maintained Service developments continued to focus on the needs and priorities of patients and families People were better informed of services There was shared responsibility and partnership. The first meeting of the Forum was held in March 2014; a core group of attendees has since met regularly with others attending on an ad-hoc basis. Participation was initially sought from patients already known to the hospice; family members and bereaved carers were also invited. The invitation was extended to members of the local community through local Healthwatch Groups with wider advertising on the hospice website and social media. Results: The Forum has contributed to many initiatives which have benefitted patients and carers including: Developing the annual patient and family satisfaction questionnaire Reviewing the 'Quiet Room' facility; contributing ideas and suggestions included in the resulting refurbishment Producing a 'How to Treat Me with Dignity and Respect' card, issued to all staff, volunteers and students as an aide memoire Evaluating food served in the hospice cafe, making recommendations to cater for lighter appetites and children Revising the inpatient information pack Contributing ideas to the Board of Trustees for an organisational 'strapline' and 'vision'. Conclusion: The group continues to meet quarterly throughout the year and is regularly asked to contribute to initiatives across the organisation. In 2016 the Hospice is taking part in the 'PLACE' assessment for the first time, with group members acting as assessors. The group provides a sounding board, a place for debate, an ideas generator and a reality check… enabling the hospice to meet the needs of our population.